Quantification of phenylalanine hydroxylase activity by isotope-dilution liquid chromatography-electrospray ionization tandem mass spectrometry - Heintz, Caroline; Blau, Nenad (Molecular genetics and metabolism, 2012)
Background: Residual phenylalanine hydroxylase (PAH) activity is the key determinant for the phenotype severity in phenylketonuria (PKU) patients and correlates with the patient's genotype. Activity of in vitro expressed mutant PAH may predict the patient's phenotype and response to tetrahydrobiopterin (BH4), the cofactor of PAH. Methods: A robust LC-ESI-MSMS PAH assay for the quantification of phenylalanine and tyrosine was developed. We measured PAH activity a) of the PAH mutations p.Y417C, p.I65T, p.R261Q, p.E280A, p.R158Q, p.R408W, and p.E390G expressed in eukaryotic COS-1 cells; b) in different cell lines (e.g. Huh-7, Hep3B); and c) in liver, brain, and kidney tissue from wild-type and PKU mice. Results: The PAH assay was linear for phenylalanine and tyrosine (r2≥0.99), with a detection limit of 105nmol/L for Phe and 398nmol/L for Tyr. Intra-assay and inter-assay coefficients of variation were <5.3% and <6.2%, respectively, for the p.R158Q variant in lower tyrosine range. Recovery of tyrosine was 100%. Compared to the wild-type enzyme, the highest PAH activity at standard conditions (1mmol/L L-Phe; 200μmol/L BH4) was found for the mutant p.Y417C (76%), followed by p.E390G (54%), p.R261Q (43%), p.I65T (33%), p.E280A (15%), p.R158Q (5%), and p.R408W (2%). A relative high PAH activity was found in kidney (33% of the liver activity), but none in brain. Conclusions: This novel method is highly sensitive, specific, reproducible, and efficient, allowing the quantification of PAH activity in different cells or tissue extracts using minimum amounts of samples under standardized conditions.